Anuário Estatístico - Statistical Yearbook 2021 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2022)
As in previous editions, the Statistical Yearbook 2021 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2017-2021 series. The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

Anuário Estatístico - Statistical Yearbook 2020 - Moçambique - Instituto Nacional de Estatística - INE (Instituto Nacional de Estatística (INE), 2021)
As in previous editions, the Statistical Yearbook 2020 contains information that makes it possible to draw a synthetic profile of Mozambique ́s socioeconomic reality in its multiple domains. It is part of the series of publications that the National Institute of Statistics (INE), in its mission to provide Mozambican society with statistical information that allows the knowledge of the reality of the country, makes available to users and the general public as a vehicle for the dissemination of the main economic, social and demographic data od Mozambique, in the 2016-2020 series The data presented in this publication are the result of the contribution of the entities of the National Statistical system (SEN) and other entities (singular and collective) that responded to the request of the INE, making possible the preparation of this publication. INE presents its thanks to all entities that contributed with data for the production of this publication and, likewise, welcomes all the collaborators, who directly or indirectly participated in the production of this work. Thanks are extended to all suggestions and criticisms of its content, which will allow us to improve future editions. Finally, INE invites the users to visit the portal for official statistics, www.ine.gov.mz, as well as the Statistical documentation Centers both in the central office and provincial delegations to enjoy the available statistical collection which is free of charge.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - portuguese / português; Northern PEA; demographics / demografia

General Elections 15 Oct 2019 Final Report - Hanlon, Joseph; Cortez, Edson; Nhancale, Sheila; Mendonça, Magda; Bande, Aldemiro; Nhacume, Nelia; Mahiquene, Telma (Centro de Integridade Pública (Public Integrity Centre), 2020)
Frelimo and President Filipe Nyusi swept away the opposition in the 15 October 2019 general elections, matching Armando Guebuza's 2009 landslide. But there were widespead reports of misconduct. On a 52% turnout, Nyusi won 73% of the vote with over 50% in all provinces. Frelimo won majorities in all provincial parliaments and in the first ever election of governors, Frelimo won all ten.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; electoral geography / geografia eleitoral

Anuário Estatístico - Statistical Yearbook 2019 - Moçambique - INE (Instituto Nacional de Estatística (INE), 2020)
À semelhança das edições anteriores, o Anuário Estatístico 2019 contém informações que permitem traçar um perfil sintético da realidade sócio-económica de Moçambique em seus múltiplos domínios. O mesmo constitui parte da série de publicações que o Instituto Nacional de Estatística (INE), na sua missão de proporcionar, à sociedade moçambicana, informação estatística que permita o conhecimento da realidade do País, disponibiliza aos utilizadores e ao público em geral, como um veículo para a disseminação dos principais dados económicos, sociais e demográficos de Moçambique, na sua maioria, na série 2015-2019.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; L - portuguese / português; Northern PEA; demographics / demografia

Regional Disparities in Fertility Preferences and Demand Satisfied for Family Planning by Modern Methods across Levels of Poverty - Assaf, Shireen; Wang, Wenjuan (USAID, 2019)
Research has highlighted disparities in family planning outcomes by wealth and by region separately. This analysis examines regional disparities within specific poverty groups. Twelve USAID family planning priority countries with recent DHS or AIS surveys were selected for the analysis, including 11 DHS surveys (Democratic Republic of Congo (DRC), Ethiopia, Ghana, Haiti, Malawi, Nepal, Nigeria, Pakistan, Rwanda Uganda, and Zambia) and one AIS survey (Mozambique). The measure of absolute poverty used in the analysis was comparable across the surveys. Households were divided into three groups to define the level of poverty: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. Two outcomes were examined for women in union: ideal number of children and demand for family planning satisfied by modern contraceptive methods. The analysis examined regional disparities in these outcomes within each of the three poverty groups using descriptive statistics, maps, and regression analyses. The results showed patterns specific to individual countries. In some countries, including Haiti, Malawi, and Rwanda, few or no regional disparities were apparent. In others, one or a few clustered regions stood out from the rest by having worse outcomes across all poverty groups (for example, Somalia region in Ethiopia). Other countries showed more regional variability in just one of the three poverty groups. This was especially true in several countries for demand for family planning satisfied by modern methods among the extremely poor and asset poor group. These results highlight the need for family planning programs to focus on specific regions where disparities exist, and on poverty groups where little of the demand for family planning is satisfied by modern methods.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Cabo Delgado Province Language Map - Translators Without Borders (Translators Without Borders, 2019)
Cabo Delgado Province Language Map
Keywords: #Map / Mapa; *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; demographics / demografia

Principais Resultados do IMASIDA 2015 - INE; INS; ICF (Instituto Nacional de Saúde (INS), Instituto Nacional de Estatística (INE), e ICF, 2018)
O Inquérito de Indicadores de Imunização, Malária e HIV/SIDA (IMASIDA 2015) em Moçambique foi realizado no âmbito de The DHS Program e vem no seguimento de quatro inquéritos anteriores, com o objectivo de determinar indicadores de saúde da mulher e da criança no país, tais como a fecundidade; gravidez e maternidade na adolescência; preferências de fecundidade; planeamento familiar; consultas pré-natais; assistência ao parto; vacinação de crianças; infecções respiratórias agudas; diarreia e tratamento das diarreias; anemia; práticas alimentares em crianças com diarreia; aleitamento em crianças; posse e uso de redes mosquiteiras; tratamento de crianças com febre; prevalência da malária e anemia nas crianças; conhecimento, atitudes e comportamentos em relação ao HIV/SIDA e cobertura de serviços de testagem de HIV; prevalência de HIV e outros indicadores associados como: o acesso e tratamento da água, saneamento básico, educação ou frequência escolar, emprego, idade na primeira união e na primeira relação sexual, empoderamento da mulher e violência baseada no género.
Keywords: G - Mozambique / Moçambique; G - north / norte; Health PEA; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; gender / género; health - maternal and child / saúde - materno-infantil; health / saúde

Fast Facts from the 2018 Mozambique MIS - The DHS Program (2018)
The 2018 Mozambique Malaria Indicator Survey (IIM) provides population-based estimates on malaria indicators to inform strategic planning and program evaluation. The 2018 LMIS is the 6th survey to be conducted in Mozambique through The DHS Program.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; M - survey / inquérito; Northern PEA; demographics / demografia; health / saúde

Regional disparities in fertility preferences and demand for family planning satisfied by modern methods across levels of poverty: Mozambique An Analysis Brief from The DHS Program - USAID (USAID, 2018)
The DHS Analytical Studies 71 examines subnational variations in fertility preferences and family planning outcomes associated with poverty in married women in 12 recent Demographic and Health Surveys. Poverty is measured based on a standard set of criteria for unsatisfied basic needs and the ownership of specific assets. Households are categorized into three poverty groups: not extremely poor, extremely poor but not asset poor, and extremely poor and asset poor. This brief summarizes the results from the Democratic Republic of The Congo based on the 2013-14 DHS on regional variations in poverty, regional estimates of mean ideal number of children, and demand for family planning satisfied by modern methods, for each poverty group among married women.
Keywords: #Reviews & Framing / Revisões e Organização; G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; G - north / norte; Health PEA; L - english / inglês; Northern PEA; demographics / demografia; gender / género; health / saúde; poverty / pobreza

Poverty and Well-Being in Mozambique: Fourth National Poverty Assessment - Ministry of Economics and Finance (Ministry of Economics and Finance - Directorate of Economic and Financial Studies, 2016)
This report provides a comprehensive analysis of poverty and well-being, including temporal trends, in Mozambique. It is based on the 2014/15 household budget survey data (Inquérito aos Agregados Familiares sobre Orçamento Familiar (IOF) 2014/15), conducted by the National Statistics Institute (Instituto Nacional de Estatística, INE). Results from this latest survey are compared to those obtained in previous survey rounds (2008/09, 2002/03 and 1996/97). We consider poverty and well-being across an array of dimensions and using two principal approaches. The first approach focuses on consumption allowing assessment of progress towards the Millennium Development Goals. The second principal approach relies on multidimensional methods for assessing poverty and well-being. The indicators employed are drawn from the four household budget surveys. They relate to education, health, housing, and possession of durable goods.
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; demographics / demografia; economic development / desenvolvimento económico; poverty / pobreza

Mozambique - Map No. 3706 Rev. 6 - United Nations (United Nations, 2016)
Map Mozambique
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - english / inglês; demographics / demografia